Age influence in the natural resistance of white rat and mice to the protozoan Toxoplasma gondii - Guerrero, Olga M (1995)
Groups of 1, 5, ID, 15 and 30 day old rats (Sprague Dawley) and Wistar mice were infected per os with different inocula of Toxoplasma gondii oocysts from an avirulent strain. Infection pattem was followed by determination of survival time, tissue lesions, parasite presence and serology. Although all the animals survived the total experimental period (30 day), there were important differences betweerr both rodents regarding to Toxoplasma natural resistance. Brain cysts, as well as tachyzoites in other organs were reg1ilarly present in mice but not in rats. On the other hand, most of the organs from mice presented characteristic T. gondii lesions, while in rats a normal tissues were observed, with the exception of an acute reaction found in the brain of a 15d old animal.